Pemberdayaan Komunitas Literasi Inovasi Indonesia (Linovesia) Jakarta Melalui Literasi Lingkungan Bertema Pengelolaan Sampah - Rahmah Purwahida; Edi Puryanto (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2026)
Empowering the Indonesian Innovation Literacy Community (Linovesia) in Jakarta through environmental literacy on the theme of waste management is a form of community service. This activity uses an ecoliteracy approach. Participants in this activity are 52 members of the Linovesia Community in Jakarta. This empowerment takes the form of literacy competency improvement training for the Linovesia Community. The methods applied are analysis, needs data collection, outreach, training, mentoring and guidance, as well as reflection and evaluation. The results achieved are the product of the application of literacy competency in the form of a digital book to practice developing literacy skills in waste management. Abstrak Pemberdayaan Komunitas Literasi Inovasi Indonesia (Linovesia) Jakarta melalui literasi lingkungan bertema pengelolaan sampah merupakan pengabdian kepada masyarakat. Kegiatan ini menggunakan pendekatan ekoliterasi. Peserta kegiatan ini merupakan anggota Komunitas Linovesia di Jakarta yang berjumlah 52 orang. Pemberdayaan ini berupa pelatihan peningkatan kompetensi literasi kepada Komunitas Linovesia. Metode yang diterapkan yaitu analisis, pendataan kebutuhan, sosialisasi, pelatihan, pendampingan dan bimbingan, serta refleksi dan evaluasi. Hasil yang dicapai yaitu produk penerapan kompetensi literasi berupa buku digital untuk berlatih mengembangkan kemampuan literasi pengelolaan sampah.